Relationship Between Arm Muscle Strength And Volleyball Overhead Service Accuracy In Athletes PBV Hizbul Wathan - Izah, Badi’ul; Purwoto, Septyaningrum Putri; Hidayatullah, Fajar; Handayani, Heni Yuli; Utami, Tri Setyo (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the relationship between upper arm muscle strength and the accuracy of volleyball upper serve in PBV Hizbul Wathan athletes. The method used is a quantitative method with a correlational approach. The subjects in this study were 15 PBV Hizbul Wathan athletes selected through a purposive sampling technique. The instruments used in the study included a push-up test to measure upper arm muscle strength and a service accuracy test to measure the accuracy of the upper serve. The results showed that the upper arm muscle strength of athletes was in the good to very good category, with an average of 24.93 push-ups, while the accuracy of the upper serve also showed high results with an average value of 29.40. Based on the Pearson correlation test, a correlation value of r = 0.839 was obtained with a significance value of p = 0.000, which indicates that there is a very strong and significant relationship between upper arm muscle strength and upper serve accuracy. It can be concluded that the greater the upper arm muscle strength an athlete has, the higher the level of upper serve accuracy that can be achieved. These findings indicate the importance of strengthening arm muscles in supporting the performance of overhead service techniques and provide implications for coaches in designing targeted physical training programs.